2013
DOI: 10.4103/0972-0707.117494
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amount of lost tooth structure and restorative technique on fracture resistance of endodontically treated premolars

Abstract: Aim:Endodontic treatment generally reduces the fracture resistance of teeth. The purpose of this study was to evaluate the fracture resistance and the mode of fracture of endodontically treated human premolars with different amounts of remaining tooth structure.Materials and Methods:Seventy non-carious human premolars were randomly assigned into 7 groups. Group 1 (ST) did not receive any preparation. The teeth in groups 2-7 received root canal treatment and different preparations. Group 2 (MO-NF): Mesio-occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…[ 4 ] Furthermore, it has been shown that direct and indirect cusp coverage adhesive restorations can significantly increase the fracture resistance of endodontically treated teeth. [ 5 ] Bonding endodontic obturation materials to radicular dentin is another approach to increase fracture resistance. [ 6 7 ] Use of sealers and lateral condensation technique significantly strengthen the roots as compared to canals, which are instrumented but not obturated.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Furthermore, it has been shown that direct and indirect cusp coverage adhesive restorations can significantly increase the fracture resistance of endodontically treated teeth. [ 5 ] Bonding endodontic obturation materials to radicular dentin is another approach to increase fracture resistance. [ 6 7 ] Use of sealers and lateral condensation technique significantly strengthen the roots as compared to canals, which are instrumented but not obturated.…”
Section: Introductionmentioning
confidence: 99%
“…As endodontic treatment in veterinary patients is generally only indicated in teeth that have undergone previous trauma, it would also be important to consider whether changes in fracture resistance are primarily due to previous trauma sustained by the tooth or due to the biomechanical changes that are directly related to endodontic therapy. Specific areas of interest would be evaluation of the effect of cyclic loading and tooth abfraction (28-30) on fracture resistance compared to the direct effects of root canal therapy, such as dentin desiccation and specific access design (14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in human dentistry have shown that endodontically treated teeth have lower fracture resistance than vital teeth (7)(8)(9)(10)(11)(12)(13). Many factors may contribute to this decreased strength including increased brittleness of dentin secondary to desiccation, removal of hard tissue during access and instrumentation, and lack of sensory feedback from the tooth (3,(14)(15)(16)(17)(18)(19)(20). However, it has been shown that the largest contributor to fracture resistance post endodontic therapy is access method, with more conservative access design conferring increased tooth strength (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For indirect restorations, different luting techniques can be employed, and the literature has shown that the use of adhesive techniques provides an increase in the fracture resistance of teeth [1,2]. Traditionally, the adhesive technique is the combination of an adhesive system with resin cement.…”
Section: Introductionmentioning
confidence: 99%